A reassessment of industrial growth in interwar Turkey through first-generation sectoral estimates. Issue 1 (2nd January 2023) - Karakoç, Ulaş
Abstract: This study presents the first sectorally disaggregated estimates of the industrial output growth for Turkey between World War I and II. These estimates indicate that at the aggregate level the existing official index overestimates the output growth. Secondly, the sectoral disaggregation shows that the industrial growth was balanced, as both textiles and food-processing branches, which comprised most of the value-added, grew significantly. Local industries expanded against the only modest gains in per capita consumption of manufactured goods and incomes. Output growth was positively correlated with higher initial import penetration and nominal protection rates, which implies that trade protectionism helped favorable relative prices induce domestic expansion. On the other hand, both import-competing and domestic-market-oriented sectors significantly expanded, which suggests that import repression and increasing domestic demand drove industrial growth.